Epithelioid sarcoma of the plantar fascia mimicking Morbus Ledderhose — A severe pitfall for clinical and histopathological misinterpretation. Issue 4 (December 2017) - Toepfer, Andreas; Harrasser, Norbert; Dreyer, Florian; Mogler, Carolin; Walther, Markus; von Eisenhart-Rothe, Rüdiger
Highlights: ES is a rare malignant mesenchymal neoplasia, preferably affecting the hand and feet. Clinical features of ES include slow growth of usually painless firm nodules. ES develops metastases in 40–50% of the cases, usually after repeated recurrences. ES should be taken into consideration as differential diagnosis of palmar and plantar fibromatosis. Abstract: Plantar fibromatosis, also known as Morbus Ledderhose, is a well known and frequently encountered disorder of the planta pedis. When conservative treatment fails, surgical therapy with complete resection is the therapeutical procedure of choice. Soft tissue sarcoma is a heterogeneous and rare malignant disease of the musculoskeletal system with over 50 histopathological subtypes which can potentially arise in any localization but is most commonly found at the extremities. Here, we report the case of an epithelioid sarcoma of the sole of the foot which was initially and repeatedly clinically and histopathologically misinterpreted as plantar fibromatosis, receiving insufficient resection and subsequently ending in amputation of the lower leg.